Assessment of the influence of physical activity and screen time on somatic features and physical fitness in 6 to 7-year-old girls - Cieśla, Elżbieta; Lelonek, Magdalena; Zaręba, Monika; Suliga, Edyta (Anthropological Review, 2021)
Aim of the study is to assess the relationship between screen time, physical activity and physical fitness among girls 6–7 years-old. 21,528 girls aged 6 and 7 from Poland were assessed in terms of physical fitness. Arm strength, abdominal strength and explosive strength of the lower limbs were measured using the EUROFIT test. Basic somatic features were measured and BMI and WHtR indices were calculated. Spontaneous and organized physical activities as well screen time were assessed by the parents utilizing a questionnaire. The multiple logistic regression method was used to evaluate the influence of screen time and spontaneous physical activity on various components of physical fitness. Physically active (PA) girls (≥1h/day) and those who participated in additional physical activities (APA) during the week had significantly higher height, weight, and BMI (p<0.001), but not WHtR. They had a higher level of flexibility, explosive strength of the lower limbs and arm strength (p<0.001). With an increase in screen time, the BMI, WHtR increased significantly and explosive strength of the lower limbs, abdominal strength and arm strength were lower. Regression analysis showed that more frequent participation in extracurricular activities increased the values of BMI and WHtR in quartile 4 (Q4), and strength components: Q2–Q4 (p<0.05). Spontaneous physical activity was positively related to the values of BMI, WHtR (both: Q4; p<0.05), explosive force of lower limbs (Q3–Q4; p=0.001), and negatively related to arm strength (Q2; p=0.001). Screen time (≥2hrs/day) increased odds for higher BMI values (p<0.05). Each screen time category decreased the odds of achieving abdominal muscle strength related to the quartiles: Q2–Q4 (p<0.05), arm strength (Q4: p<0.05). ST (1 <2hrs/day) decreased arm strength (Q3; p= 0.045). Our research has shown that screen time-related sedentary behavior and physical activity affect overweight and obesity indices (especially BMI) and strength abilities. The observed associations more often affected girls with a higher level of fitness The results observed in girls aged 6-7 indicate a need for early intervention aimed at limiting time spent watching TV and computer use, as well as to encourage both spontaneous and organized physical activities.